2019
DOI: 10.1097/01.ogx.0000569248.49687.19
|View full text |Cite
|
Sign up to set email alerts
|

Routine First-Trimester Screening for Fetal Trisomies in Twin Pregnancy: Cell-free DNA Test Contingent on Results From Combined Test

Abstract: (Abstracted from Ultrasound Obstet Gynecol 2019;53(2):208–213) In singleton pregnancies, screening for the major trisomies using a combination of fetal nuchal translucency (NT) thickness, serum β-human chorionic gonadotropin, and pregnancy-associated plasma protein A can detect approximately 90% of cases of trisomy 13, 18, or 21, at a false-positive rate of 5%. In twin pregnancies, use of the combined test can achieve a similar detection rate (DR) for trisomy 21, but with a higher false-positive rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The literature search identified 381 potentially relevant citations, but 366 were excluded because they were not relevant, a conference abstract rather than a peer‐reviewed paper, a review article, an opinion, not confined to twins, a case–control study, a study on clinical implementation of cfDNA testing in screening for aneuploidy in which pregnancy outcome data were provided for fewer than 85% of the study population or a proof‐of‐principle study reporting laboratory techniques rather than clinical validation of a predefined method of maternal blood cfDNA analysis (Figure 2). In total, 15 relevant studies were identified 2,13–26 but three of these 2,13,14 were excluded from the meta‐analysis because their data are included in the updated FMF results presented above. The characteristics of our current study and the 12 studies identified by the literature search are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search identified 381 potentially relevant citations, but 366 were excluded because they were not relevant, a conference abstract rather than a peer‐reviewed paper, a review article, an opinion, not confined to twins, a case–control study, a study on clinical implementation of cfDNA testing in screening for aneuploidy in which pregnancy outcome data were provided for fewer than 85% of the study population or a proof‐of‐principle study reporting laboratory techniques rather than clinical validation of a predefined method of maternal blood cfDNA analysis (Figure 2). In total, 15 relevant studies were identified 2,13–26 but three of these 2,13,14 were excluded from the meta‐analysis because their data are included in the updated FMF results presented above. The characteristics of our current study and the 12 studies identified by the literature search are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 12 studies reporting on screening for trisomy in twin pregnancies by cfDNA testing of maternal blood, in addition to our previous studies, the data from which are included in the current FMF study. The main features of these 12 studies are, first, the method of cfDNA testing was by MPSS in 11 studies and by targeted testing in only one, second, none of the studies was confined to the first trimester and, in some cases, testing was carried out as late as 36 weeks' gestation 16,26 , and, third, in nine of the studies, the cfDNA test provided a result in > 99% of cases 15–18,20,22,23,25,26 and, in six of the studies, pregnancy outcome was apparently obtained in > 99% of cases 14,16,18,21,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…For over a decade, the first-trimester combined test, including maternal age, fetal NT and maternal serum biochemistry, with a detection rate of 90% at a FPR of 5%, has played a major role in screening for trisomy 21 in the first trimester of pregnancy. In recent years, cell-free (cf)DNA testing has improved significantly the performance of screening for trisomy 21, with a detection rate of > 99% at a FPR of < 0.1% [21][22][23][24] . However, the cost of cfDNA testing is high, making it impossible to offer it to all pregnant women.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…55,58 Any one or more of the fetal fraction measurement methods have been used in combination with whole-genome or targeted cfDNA aneuploidy screening tests (Table 3). 69 While some programs use a fixed fetal fraction cut-off to determine adequacy, other methods are also utilized. In multifetal pregnancies, this cut-off is dependent on whether total fetal fraction or individual fetal fraction is measured and whether the twins are likely monozygous or likely dizygous.…”
Section: Fetal Fraction Measurements Among Multiple Pregnanciesmentioning
confidence: 99%